The Awareness On Waqf Al-Manqul At Mosques Among Rural Areas Muslim Community In Kubang Pasu, Kedah - Halisatun Nadiya, Salim (2019)
Islam demands each Muslim to practice altruism in the name of justice and brotherhood. One way to implement this is through the practice of waqf among Muslims. Waqf is a form of charity that have special features in terms of permanence and continuity. One of the categorization of waqf is movable waqf (waqf al-manqul). Waqf al-manqul at mosques is known as a waqf of movable property at mosques such as al-Quran, prayer mat, prayer veil, corpse van, furniture, religious reading material, water filter, air conditioner and etc. It gave a lot of benefits from the waqf property (mawquf) for years, generations or even centuries to the Muslim community (mawquf alayhim). The ownership of waqf is withdrawn from its owner and returned to Allah for the benefit of the subjects to which the property has been granted. While Malaysia is growing and expanding rapidly in line with globalization, but the level of awareness on waqf almanqul at mosques is still considered unsatisfactory and moderate. This research paper aims to study the awareness on waqf al-manqul at mosques among rural areas Muslim community in Kubang Pasu, Kedah. Six mosques at mukim Temin in Kubang Pasu, Kedah have chosen as a population and a total number of 169 respondents were involved in this study. The study founds there is significant relationship between religious values and social influences; and the awareness on waqf al-manqul at mosques. Meanwhile, religious values is the most influence factors that influence the awareness on waqf al-manqul at mosques among rural areas Muslim community in Kubang Pasu, Kedah.